(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Teaching non-mathematics subjects is an extensive problem with repercussions for effective learning and teaching. This study investigated the experiences of junior high school mathematics teachers in teaching non-mathematics subjects. It utilized descriptive-qualitative research. It employed a thematic analysis of the teachers’ experiences teaching non-mathematics subjects. Results showed that non-mathematics subjects are given to young and beginning mathematics teachers with limited related training in full-load teaching and handling above-average class sizes. Complete the teaching load and mismatch of teacher needs in the hiring process are the main reasons why there are mathematics teachers who teach non-mathematics subjects. The identified best practices are accepting it as a challenge, doing much reading, searching on the net, and being willing to ask for help. Teachers need to keep grounded, be confident, and be adept at delivering whatever subjects are given to them.